2016
DOI: 10.1177/0266666916671984
|View full text |Cite
|
Sign up to set email alerts
|

Unfulfilled need

Abstract: The ubiquity of information and communication technologies (ICT) in all aspects of life has an important consequence in today's world: shortage of skilled personnel in this area. Although the dotcom bubble in 2000 had an adverse effect in the requirement for ICT skills in industrialized countries, this is not applicable for many developing countries, where ICT skills are in high demand. Even though South Africa is one of these countries, ICT enrolments and graduations do not meet ICT skills demand. An importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Recently, digitisation changed the way organisations perceive the importance of ICT skills in the labour market [4]. Especially as ICT careers are the most crucial professions around the world, the high demand for ICT professionals in the labour markets has shown that there is a shortage of skilled ICT professionals in South Africa [2,18]. Information and Communication Technology careers include software development, information technology (IT) audit, IT infrastructure and architecture, IT change management, database development, system design, business analysis, ICT network support and other technical skills in high demand in organisations [2,19].…”
Section: Ict Skills Required For the Labor Marketmentioning
confidence: 99%
“…Recently, digitisation changed the way organisations perceive the importance of ICT skills in the labour market [4]. Especially as ICT careers are the most crucial professions around the world, the high demand for ICT professionals in the labour markets has shown that there is a shortage of skilled ICT professionals in South Africa [2,18]. Information and Communication Technology careers include software development, information technology (IT) audit, IT infrastructure and architecture, IT change management, database development, system design, business analysis, ICT network support and other technical skills in high demand in organisations [2,19].…”
Section: Ict Skills Required For the Labor Marketmentioning
confidence: 99%
“…The authors consider technology as a growth source for African economies. It is widely known that most developed countries in the region, such as South Africa and Egypt, are countries with a low technological base [21], [12], wherein Egypt is one of the main financial assistance recipients from development institutions [17]. For South Africa, the most profitable option may be to obtain high technologies in the processing ores and raw materials field.…”
Section: Technology Development In Africa -Prospectsmentioning
confidence: 99%
“…South Africa is a developing country where IT skills are in high demand. These IT skills are not met by Higher Education Institutions' IT graduate numbers [14,22].…”
Section: Literature Reviewmentioning
confidence: 99%